2021
DOI: 10.1021/acs.chemrestox.0c00486
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Human Lung Cells to Polystyrene Microplastics Significantly Retards Cell Proliferation and Triggers Morphological Changes

Abstract: Microplastics in the environment produced by decomposition of globally increasing waste plastics have become a dominant component of both water and air pollution. To examine the potential toxicological effects of microplastics on human cells, the cultured human alveolar A549 cells were exposed to polystyrene microplastics (PS-MPs) of 1 and 10 μm diameter as a model of the environmental contaminants. Both sizes caused a significant reduction in cell proliferation but exhibited little cytotoxicity, as measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(95 citation statements)
references
References 66 publications
6
86
2
1
Order By: Relevance
“…Taken together, this means that the overall toxicity of MPs can be extremely variable. Studies specifically designed to assess the health risk of mixtures of different vehicles and adsorbed xenobiotics are still poor because most of the uptake data on MPs have been obtained from mammalian studies that use virgin polystyrene (PS) MPs in in vivo and in vitro models [ 27 , 28 , 29 , 30 , 31 , 32 ]. After oral ingestion, MPs can cross the intestinal barrier and reach the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, this means that the overall toxicity of MPs can be extremely variable. Studies specifically designed to assess the health risk of mixtures of different vehicles and adsorbed xenobiotics are still poor because most of the uptake data on MPs have been obtained from mammalian studies that use virgin polystyrene (PS) MPs in in vivo and in vitro models [ 27 , 28 , 29 , 30 , 31 , 32 ]. After oral ingestion, MPs can cross the intestinal barrier and reach the systemic circulation.…”
Section: Introductionmentioning
confidence: 99%
“… MPs translocation from the lung to the placenta 20 nm Polypropylene Intratracheal instillation during gestation 2.64 × 10 14 MPs, 24 h The exposure resulted in the translocation of MPs to placental and fetal tissues and rendered the fetoplacental unit vulnerable to adverse effects [ 57 ] MPs in human-derived cells 25–200 μm Polypropylene Addition to cultures (media) of somatic cells, blood cells, and murine immune cells 0.1–4.5 mg per well, 24 h MPs induced and triggered pro-inflammatory cytokines that caused a local immune response [ 51 ] MPs and various phthalate esters (PAEs) on human lung epithelial cells 100 nm Polystyrene Addition to cells MPs at 10, 20, 100, 200, 500 or 1000 μg mL −1 , 24 h Cells exhibited changes in viability, oxidative stress, and inflammatory reaction. [ 52 ] MPs on human cells 1 and 10 μm Polystyrene Addition to cells 0.05–100 μg mL −1 , 24, 48, 72, and 96 h Exposure significantly retards cell proliferation and triggered morphological changes [ 53 ] MPs in human-derived cells 5−25 μm, 25–75 μm, and 75–200 μm Polystyrene Dispersed in cell culture medium 1000, 100, and 10 μg mL −1 , 1 day and 4 days MPs increased acute inflammation, cell death by chemical toxicity, and induced cell membrane damage by physical toxicity [ 54 ] MPs on human intestinal epithelial cells 0.05–0.1 μm and 0.04–0.09 μm Polystyrene Exposure in cell culture medium 1–100 μg mL −1 , 24 or 48 h Cells uptake and internalized MPs, however, no toxic effects were observed. [ 55 ] MPs on human lung epithelial cell 25 nm and 70 nm Polystyrene Dispersion in cell medium 2.5–300 μg mL −1 , 24 h MPs significantly affected cell viability, activated inflammatory gene transcription, and changed the expression of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…But the adsorption and persistence of NPs on the skin and their effects on keratinocytes are understudied. Recently, several studies focused on the impacts of unintentionally exposed NPs via ingestion [31] or inhalation route [32]. But very few studies have demonstrated the penetration and accumulation tendency of polymeric NPs on inflamed skin [33,34].…”
mentioning
confidence: 99%